Where the lilies bloom - Cleaver, Vera; Cleaver, Bill.; Spanfeller, James J. 1930-. (Philadelphia J. B. Lippincott, 1969)
In the Great Smoky Mountains region, a fourteen-year-old girl struggles to keep her family together after their father dies.
In the Great Smokey Mountain region, a fourteen-year-old girl struggles to keep her family together after their father dies.
Keywords: Brothers and sisters -- Fiction; Great Smoky Mountains (N.C. and Tenn.) -- Fiction